Monotheism between pagans and Christians in late antiquity - Mitchell, Stephen.; Van Nuffelen, Peter. (Interdisciplinary Studies in Ancient Culture and Religion ;)
Summary : The fourth century was a major religious battleground. The rise of Christianity, and in particular its dominance from Constantine onwards, marked an important shift in the religious history of the Mediterranean. Christianity saw this change as the victory of its monotheism over the polytheism of paganism. This volume studies how similarities between paganism and Christianity were obscured in the polemic that was waged by Christianity against paganism and in the pagan responses to it. The volume includes papers on Porphyry, Augustine, Themistius, Latin verse inscriptions, as well as dealing with the different ways in which Christian and pagan thinkers conceived of monotheism. A recurring theme in the papers shows that a concrete religions issue lay at the heart of such polemic: who can worship?